Investors' footsteps: an empirical study of herd behaviour in the stock exchanges of Bosnia and Herzegovina, Serbia and Ukraine - Keskin, Meltem; Ayture, Selma (Journal of Asian Scientific Research, 2025)
Herding behaviors can distort the Capital Asset Pricing Model (CAPM) and lead to deviations of assets from their real values, thus resulting in purchases and sales at incorrect prices. In this study, the existence of herding behaviors was examined in the stock exchanges of Bosnia and Herzegovina, Serbia, and Ukraine using three different and widely accepted models. These countries were selected due to their status as candidate countries for the European Union (EU). The study assesses the success of the structural reforms undertaken by these countries in the post-socialist period, the extent to which their market regulations align with those of the European Union, and whether market efficiency has been achieved during the accession process. Herding behavior is considered one of the indicators of market efficiency. The analysis utilized daily closing prices from January 2010 to October 2024. The results revealed no substantial indication of herding behavior in the stock markets of the three EU candidate countries when assessed through the models developed by Christie, Huang, Hwang, and Salmon. However, applying the approach of Chang, Cheng, and Khorana, statistically significant signs of sentiment-driven herding were detected exclusively in the stock market of Bosnia and Herzegovina.